Image-Guided Microneurosurgical Management of Small Arteriovenous Malformation: Role of Neuronavigation and Intraoperative Doppler Sonography - Akdemir, H.; Öktem, S.; Menkü, A.; Tucer, B.; Tuğcu, B.; Günaldi, O. (min - Minimally Invasive Neurosurgery, 2007)
Introduction: The goal of this study was to evaluate the efficacy and reliability of neuronavigation and intraoperative microvascular Doppler sonography (MDS) for identifying afferent (feeding) and efferent (draining) vessels as well as for controlling the totality of the surgical resection of arteriovenous malformations (AVMs).Methods: Between June 2000 and November 2005, twenty-five patients with small arteriovenous malformations (grades I-III) underwent microsurgical removal at our institution. A passive-marker-based neuronavigation system (Brain Lab, Munich, Germany), and an intraoperative MDS (Multi Dop X system, DWL, Germany) were used in this surgery. Blood flow velocities (BFV) in afferent and efferent vessels were recorded before and after removal of AVM. The preoperative neurological status and postoperative outcome were recorded. Patient follow-up monitoring ranged from 4 months to 3 years (mean: 16 months).Results: The calculated registration accuracy of the neuronavigation computer ranged between 0.2-1.7 mm (mean: 1.1 mm). Before AVM removal the mean BFV of afferent vessels was 56.5±13.4 (28-98 cm/s) and the PI varied by 0.40±0.11 (0.25-0.66), after AVM removal these values reduced to 4.8±0.8 cm/s and 0.26±0.05, respectively. Similarly, before AVM removal, the mean BFV of efferent vessels was 13.5±4.5 (4-20 cm/s) and PI was 0.4±0.2 (0.34-0.56), after AVM removal both BFV and PI were not recorded. Complete removal of the AVMs was accomplished in 24 (96%) out of 25 patients which was confirmed with postoperative digital subtraction angiography (DSA). While there was no mortality, three patients (12%) had a worsening in their neurological status after surgery.Conclusion: Image-guided microneurosurgery with intraoperative MDS is a safe, effective, and reliable method for identifying the afferent and efferent vessels and for confirming the complete resection of AVMs. These benefits of image-guided microsurgery were most apparent for small, deep-seated AVMs that were not visible on the surface of the brain. In addition these techniques reduce the operative time and blood loss during AVM resection.
Keywords: arteriovenous malformation; intraoperative Doppler sonography; neuronavigation; clinical outcome